A Universal Mental Health Promotion Programme for Young People in Italy. (25th August 2015) - Gigantesco, Antonella; Del Re, Debora; Cascavilla, Isabella; Palumbo, Gabriella; De Mei, Barbara; Cattaneo, Chiara; Giovannelli, Ilaria; Bella, Antonino
Abstract : In Italy, the Mental Health Unit of the National Institute of Public Health has developed a school-based mental health programme based on a structured handbook. The aim of this programme is to promote self-efficacy, psychological well-being, and life satisfaction. In this study, we evaluated the effectiveness of this programme. We used data from 308 students who participated in a study in 9 Italian high schools during the 2011-2012 school year. In order to analyse the school intervention programme, we set up a pre-post test design study involving 18 classrooms (8 of which acting as a control). The schools were selected via a snowball technique, and then the classrooms that agreed to participate were randomly assigned to intervention and control groups. The programme was performed during regular school hours in one-hour a week sessions for a total of 20 hours of classroom time. Assessments before and 2 months after the programme were performed using Regulatory Emotional Self-Efficacy, Satisfaction With Life, and Ryff's Psychological Well-Being Scales. The results showed an improvement in self-efficacy in regulating negative affect, overall psychological well-being, and satisfaction with life. These results demonstrate that the programme produced significant positive effects on the mental health status of participating students.